Global health challenges and the world economy: Assessing the benefits of fiscal policy cooperation - Pierre-Richard Agénor (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
In the midst of the COVID-19 health crisis, many observers advocated the implementation of a global strategy to promote the production and equitable distribution of vaccines, prevent the emergence of infectious diseases, and reduce the risk of future pandemics. But what are the implications of this strategy for national tax and spending policies, and the world economy? What is the role, if any, of fiscal policy cooperation in that context? Dwelling on recent analytical research, it is argued that cooperation can be welfare-improving for the world at large, even when taxation is distortionary and governments face a trade-off between financing local public goods (such as infrastructure) and global public goods (vaccines). This is also the case when the levy used to finance the production of global public goods takes the form of a wealth tax, even under a high degree of financial openness. Moreover, optimal tax rates are not necessarily higher under coope-ration - an important consideration from a policy perspective.
Keywords: 330